Magnetically Guided Protein Transduction by Hybrid Nanogel Chaperones with Iron Oxide Nanoparticles. (13th June 2016) - Kawasaki, Riku; Sasaki, Yoshihiro; Katagiri, Kiyofumi; Mukai, Sada‐atsu; Sawada, Shin‐ichi; Akiyoshi, Kazunari
Abstract: Protein pharmaceuticals show great therapeutic promise, but effective intracellular delivery remains challenging. To address the need for efficient protein transduction systems, we used a magnetic nanogel chaperone (MC): a hybrid of a polysaccharide nanogel, a protein carrier with molecular chaperone‐like properties, and iron oxide nanoparticles, enabling magnetically guided delivery. The MC complexed with model proteins, such as BSA and insulin, and was not cytotoxic. Cargo proteins were delivered to the target HeLa cell cytosol using a magnetic field to promote movement of the protein complex toward the cells. Delivery was confirmed by fluorescence microscopy and flow cytometry. Delivered β‐galactosidase, inactive within the MC complex, became enzymatically active within cells to convert a prodrug. Thus, cargo proteins were released from MC complexes through exchange interactions with cytosolic proteins. The MC is a promising tool for realizing the therapeutic potential of proteins.